Main varieties of bread (Triticum aestivum L.) and durum (Triticum durum Desf.) wheat. - М. П. Чебаков (Plant Varieties Studying and Protection)
Results of systematization and morphological characteristics of two wheat species-bread (Triticum aestivum L.) and hard (Triticum durum Desf.) are given. Detail descriptions of 55 main varieties of bread wheat and 32 varieties of hard wheat arep- resented in table version. In practical application these result enable plant breeders, seed producers and variety testers to determine wheat varieties easily sinse it is method for morphological systematics of wheat.